Comparative Study of the Layered Perovskites Pr1−xA1+xCoO4, (A = Sr, Ca). Issue 11 (4th August 2014) - Hassen, Arafa; Krimmel, Alexander; Mandal, Prabhat; Damjanovic, D.
<x xml:space="preserve">Abstract</x> We present structural, magnetic, and electric properties of Pr1−xCa1+xCoO4 layered perovskites and compare them with the results of recently studied Pr1−xSr1+xCoO4. The Rietveld refinements of X‐ray powder diffraction (XRD) patterns indicate that all samples crystallize in the K2NiF4‐type structure with space group symmetry I4/mmm. The parent compounds Pr(Ca, Sr)CoO4 are paramagnetic insulators. Upon increasing x, a variety of different magnetic transitions can be identified. The complex magnetic behavior results from the interplay of competing interactions. The temperature‐dependent electrical resistivity of the samples shows 2D variable range hopping (2D‐VRH). The results are discussed with respect to structure−property relationships.